Visual Culture-Based Learning for K-2 Children in Bandung: A Relevant Implementation Study - Mohamad Helmi Ismail; Nurul Hidayah; Ririn Despriliani (AL-ISHLAH: Jurnal Pendidikan, 2024)
Early Childhood Education (ECE) often lacks integration of visual arts, which are critical for fostering holistic development and promoting children’s engagement as active citizens in their communities. This study addresses the relevance of a visual arts-based learning model in kindergarten education. Employing a descriptive case study with an embedded single-case design, the study examines the integration of visual culture in the curriculum of a second-grade kindergarten class. Grounded analysis and pattern matching techniques were utilized to assess the learning model's relevance. The findings indicate that the visual culture-based learning model aligns with the developmental needs of K-2 students, addressing both cognitive and socio-emotional growth. The model facilitates an inclusive approach that enhances the overall kindergarten learning experience. The theoretical model developed through this study provides foundational insights for further research in the underexplored area of visual arts in ECE. It challenges traditional views that often regard visual arts-based learning as problematic at this level, offering a reconceptualization that aligns with children's developmental needs. This research underscores the necessity of integrating visual arts into kindergarten education, providing an empirical basis for future studies and reconsidering current pedagogical practices. The constructed model serves as both a practical framework and a theoretical contribution to early childhood education literature.